Relationship between job burnout and mental health of nurses working in province of Qom - Abolghasem Pourreza; Mohammad Reza Monazam; Marzieh Abassinia; Mehdi Asghari; Hosein Safari; Mohammad Sorani; Farhad Habibi (Tehran University of Medical Sciences, 2012)
Background: Job Burnout is one of the important factors to reduce productivity, making mental and physical adverse effects on jobs related to human services and losing efficient manpower by considering the important role of nurses in the health care systems. This study has been done to survey the association between mental health and job burnout syndrome among nurses' staff in training hospitals in Qom province.Materials & Methods: This is an analytic-descriptive study which has been performed among 200 nurses personnel in the training hospitals of Qom province with applying proboblity multistage statistical method.Three quetionnaires including demographic data,general health and Maslach,s Burnout questionnaire (Inventory) were used to data gathering by which validity and reliability were certified in the previous studies. Data analyzed by SPSS18. Descriptive statistics such as frequency, percentage, inferential statistics (Chi-square test and correlation coefficient of spearman and pearson) and also man-whitney test applied.Results: Average score of job burnout was 60.8. Respecting general health, 53% of nurses was in danger. Average score of emotional fatique,the personalization and personal accomplishment was 27.2,12.17 and 21.7,respectively. 50 percent of nurses had physical dysfunction,44.5% suffered from anxiety and sleep disorders, 32.5 and 44.5% had social dysfunction and depression, respectively. There was a significant correlation between burnout syndrome and general health. Based on the spearman correlation test, there was a significant correlation between emotional fatique and physical disorders, anxiety and sleep disorders and social dysfunction.Conclusion: Regarding srtessful nature of nursing job and high prevalence of disorders in general and mental health of nurses incomparision to others and also high prevalence of burnout among nurses in Qom province,it is nesecary to decrease these sort of problems through applying arrangements such as enhancing motivation, increasing work stability, increasing job satisfaction, clearance in how individuals respond to take actions and tasks division among personnels to reduce workload.